Mechanism of extracellular space changes in cryptococcal brain granuloma revealed by MRI tracer - Abulikemu, Nuerbiyemu; Gao, Xin; Wang, Wei; He, Qingyuan; Wang, Gang; Jiang, Tao; Wang, Xiaodong; Cheng, Yumeng; Chen, Min; Li, Yanran; Liu, Lulu; Zhao, Jingjing; et al. (Frontiers in Neuroscience, 2022)
Purpose：To investigate the changes of extracellular space in cryptococcal brain granuloma and it’s pathological mechanism. Material and methods：The animal model of cryptococcal brain granuloma was established by injecting 1x106CFU/ml Cryptococcus Neoformans type A suspension into the caudate nucleus of Sprague Dawley rats with stereotactic technology. The infection in the brain was observed by conventional MRI scanning on days 14, 21 and 28 of modeling. The tracer-based MRI with a gadolinium-diethylene triamine pentaacetic acid (Gd-DTPA) as magnetic tracer was performed on the rats with cryptococcal granuloma and the rats in the control group. The parameters of extracellular space (ECS) in each area of cryptococcal brain granuloma were measured. The parameters of ECS in the two groups were compared by independent sample t-test, and the changes in ECS and its mechanism were analyzed. Results: Up to 28 days of modeling, the success rate of establishing the brain cryptococcal granuloma model with 1x106CFU/ml Cryptococcus Neoformans suspension was 60%. In the internal area of cryptococcal granuloma, the effective diffusion coefficient D* was significantly higher than that of the control group (t = 2.76, P < 0.05), and a same trend showed in the volume ratio α (t = 3.71, P < 0.05), the clearance rate constant k (t = 3.137, P < 0.05) and the tracer half-life T1/2 (t = 3.837, P < 0.05). The tortuosity λ decreased compared with the control group (t = -2.70, P < 0.05); At the edge of the cryptococcal granuloma, the D* and α decreased while the λ increased compared with the control group (D* : t = -6.05, P < 0.05; α: t = -4.988, P < 0.05; λ: t = 6.222, P < 0.05) . Conclusion: The internal area of the lesion demonstrated a quicker, broader and more extended distribution of the tracer, while the edge of the lesion exhibited a slower and narrower distribution. MRI tracer method can monitor morphological and functional changes of ECS in pathological conditions and provide a theoretical basis for the treatment via ECS.